PECULIARITIES OF UKRAINEN LOCAL BUDGETS’ FUNCTIONING IN CONDITIONS OF THE COVID – 19 PANDEMIC - Vartsaba , V.I.; Mulesa , E.V.; Furik, I.I. (The actual problems of regional economy development, 2021)
The aim of the article is to study the specifics of formation and distribution of Ukrainian local budgets financial resources under the influence of the COVID-19 pandemic, its financial and economic consequences for sustainable development and justification of measures to overcome new challenges and threats caused by the 2020 crisis. The set of general scientific and applied research methods was used, in particular: general scientific methods of analysis and synthesis, induction and deduction - to generalize the features of socio-economic development of local communities, highlight the patterns of filling and use of their budgets in terms of budget innovations the emergence and spread of coronavirus disease, improving the promotion of further development of territories and the formation of conclusions; comparative method - when analyzing the criteria for the functioning of local budgets before and after the pandemic; quantitative analysis - in identifying modern features of local budget development; economic-mathematical modeling - to substantiate the impact of coronavirus disease on the socio-economic development of territories in terms of financial decentralization, etc. The analysis of the formation peculiarities and distribution of Ukrainian local budgets financial resources in recent years showed that the economic losses caused by quarantine and changes in current legislation in connection with COVID-19, negatively affected their functioning. Local budgets have suffered significant losses due to reduced economic mobility of tax revenues (personal income tax, land fees, reduction of single tax rates for groups I and II of taxpayers, etc.). However, after the introduction of adaptive quarantine, the revenue side of local budgets began to grow, which led to the resumption of economic activity of small and medium-sized businesses. However, given the projected reduction in the revenue side of the budgets of all levels caused by the pandemic, as well as the limited revenues of the State budget, the issue of reviewing local government expenditures and finding alternative sources of filling them is acute. The scientific novelty lies in the disclosure of fundamentally new criteria for the development of local budgets in the current conditions of the existing coronavirus crisis and proving its direct impact on the development of territories in general. The practical significance of the obtained results lies in the novelty of reasonable ways to overcome the negative effects of the COVID-19 pandemic on the revenue and expenditure side of local budgets as effective ways to regulate the fiscal mechanism and intergovernmental relations in general.